Patterning of the Autotrophic, Mixotrophic, and Heterotrophic Proteomes of Oxygen-Evolving Cyanobacterium Synechocystis sp. PCC 6803 - Muth-Pawlak, Dorota; Kreula, Sanna; Gollan, Peter J.; Huokko, Tuomas; Allahverdiyeva, Yagut; Aro, Eva-Mari (Frontiers in Microbiology, 2022)
Proteomes of an oxygenic photosynthetic cyanobacterium Synechocystis sp. PCC 6803 were analyzed under photoautotrophic (low and high CO2, assigned as ATLC and ATHC), photomixotrophic (MT) and light activated heterotrophic (LAH) conditions. Allocation of proteome mass fraction to seven sub-proteomes as well as differential expression of individual proteins were analyzed, paying particular attention to the photosynthesis and carbon metabolism centered sub-proteomes affected by the quality and quantity of the carbon source and the light regime upon growth. A distinct common feature of the ATHC, MT and LAH cultures was a low abundance of the inducible carbon concentrating mechanisms and photorespiration related enzymes, independently of the inorganic or organic carbon source. On the other hand, these cells accumulated respiratory NAD(P)H dehydrogenase I complex (NDH-11) in the thylakoid membrane (TM). Additionally, in glucose supplemented cultures a distinct NDH-2 protein, NdbA, accumulated in the TM whilst the plasma membrane localized NdbC and terminal oxidase decreased in abundance in comparison to both AT conditions. Photosynthetic complexes were uniquely depleted under the LAH condition while accumulated under ATHC. MT proteome displayed several heterotrophic features typical of the LAH proteome, particularly including the high abundance of ribosome as well as amino acid and protein biosynthesis machinery-related components. It is also noteworthy that the two equally light-exposed ATHC and MT cultures allocated similar mass fractions of the total proteome to the seven distinct sub-proteomes. Unique, trophic condition-specific expression patterns were likewise observed among individual proteins, including the accumulation of phosphate transporters and polyphosphate polymers storing energy surplus in the highly energetic bonds under MT condition and accumulation under LAH of enzyme catalyzing cyanophycin biosynthesis. It is concluded that the rigor of cell growth in MT condition results to a great extent from combining of photosynthetic activity with high intracellular inorganic carbon conditions created upon glucose breakdown and release of CO2, beside the direct utilization of glucose-derived carbon skeletons for growth. This combination provides the MT cultures with excellent conditions for growth that often exceeds that of the mere ATHC.